Injection molding electroluminescent components. Issue 7 (22nd December 2012) - Middleton, B.; Goodship, V.
Abstract This article explores the feasibility of using mass manufacture, namely injection molding, as a route to produce cost effective electroluminescent (EL) components straight from the mold tool. EL screen printing pastes were adapted and introduced into the injection molding environment as a multilayer structure. Four‐layer systems were investigated using a spray deposition method to apply individual layer components directly in‐mold. Finally, the substrate was back injected to produce a three‐dimensional illuminating device straight from the mold tool. Materials, methods, and outcomes are described, the implication being that electronic manufacture could be moved upstream and performed in‐mold with resultant cost and energy savings. POLYM. ENG. SCI., 2013. © 2012 Society of Plastics Engineers